Case report and literature review: Small bowel intussusception due to solitary metachronous metastasis from renal cell carcinoma - Yang, Wenming; Cai, Zhaolun; Nie, Pan; Yuan, Tao; Zhou, Hang; Du, Qiang; Qiu, Siyuan; Zhang, Jianhao; Yang, Lie (Frontiers in Oncology, 2022)
Introduction Solitary metachronous small bowel metastasis from renal cell carcinoma (RCC) is rare. In contrast to idiopathic intussusception frequently occurring in children, adult intussusception is fairly uncommon and usually indicates a malignancy. Case presentation We presented an 84-year-old man with small bowel intussusception and obstruction due to a solitary metachronous metastasis from RCC. Computed tomography with intravenous contrast revealed small bowel obstruction and a 4 × 4 cm intraluminal soft-tissue mass with moderate enhancement. During urgent exploratory laparotomy, a pedunculated tumor of the distal ileum was found to be the lead point of intussusception. Hence, reduction of the intestinal invagination and segmental resection of the ileum with functional end-to-end anastomosis were performed. Histological examination finally confirmed the diagnosis. The postoperative recovery was uneventful. The patient was discharged without any complications on postoperative day 6. Conclusion The case report highlights the rarity of solitary metachronous small bowel metastases from RCC and suggests that life-long follow-up of RCC patients is critical due to its unpredictable behavior and the possibility of a long period of dormancy. Complete surgical resection remains the mainstay treatment for such patients.